Urban–Rural Cultural Contexts and Community-Based Vector Surveillance: Social Dimensions of Dengue Prevention through Larval Monitoring Cadres in Indonesia - Ernawati, Kholis; Wulansari, Rifda; Kinanthi, Melok Roro; Nursanti, Ade; Caninsti, Riselligia (Journal of Cultural Analysis and Social Change, 2026)
Community-based disease prevention initiatives are deeply embedded within local cultural, social, and spatial contexts. In dengue-endemic countries such as Indonesia, larval monitoring cadres (Juru Pemantau Jentik) play a pivotal role not only as technical health volunteers but also as community actors navigating diverse social norms, collective practices, and institutional structures. This study examines how urban and rural socio-cultural contexts shape the perceptions, performance, and enabling conditions of larval monitoring cadres in dengue prevention efforts. Using a comparative cross-sectional design, quantitative data were collected from cadres operating in an urban sub-district (Kemayoran, Jakarta) and a rural sub-district (Kresek, Banten). Guided by the PRECEDE–PROCEED framework, the analysis assessed predisposing, enabling, and reinforcing factors influencing cadre performance. Descriptive statistics and Fisher’s Exact Test were employed to identify differences between urban and rural settings. The findings reveal statistically significant disparities in cadre performance and perceived enabling factors across urban and rural contexts. Urban cadres demonstrated higher performance levels, supported by stronger institutional facilitation and programmatic resources, whereas rural cadres operated within more limited structural support despite strong community embeddedness. These differences reflect not merely technical gaps, but broader socio-cultural and structural variations related to patterns of community participation, social capital, and local governance. This study contributes to interdisciplinary debates on culture and social change by demonstrating how public health interventions function as sites of social negotiation, where cultural norms, spatial inequality, and institutional arrangements intersect. By reframing community-based dengue prevention as a socio-cultural process rather than a purely technical endeavor, the article offers insights for culturally responsive health governance and sustainable community empowerment in the Global South.